The assessment of pain, flexibility and daily activity level in the patients who had facet tropism - Kizilkan, Busra; Sayaca, Cetin; Turkoglu, Ozlem (International Journal of Scientific Reports, 2020)
Background: The aim of this study to investigate the relationship between asymmetric angular value in lumbar facet joints and pain, flexibility and daily activity level. Methods: The study included 51 patients with complaint of low back pain (LBP) and underwent lumbar magnetic resonance imaging. Facet joint angle measurements of L4-L5 and L5-S1 were measured. Visual analogue scale (VAS) was used for severity of pain. Joint range of motions (ROM) was measured via goniometry. Body extensibility measurements were performed via body hyperextension test. The Nottingham health profile scale was used to assess daily activity level of individuals. Results: The VAS values of patients with tropism were significantly higher (p=0.016). There wasn’t significance difference in ROM and flexibility (p=0.784). In patient group with facet tropism, there was limit of lateral flexion towards the side where the facet joint angle was larger than the control group (p=0.002). There was no significant difference between daily activity levels of both groups (p=0.755). Conclusions: Pain severity of facet tropism patients is higher. Patients with facet tropism had lateral flexion restriction. In the light of these findings, when the lateral flexion limitation is detected in individuals with complaints of pain without discopathy, it’s necessary to make MR measurements in differential diagnosis by considering facet joint tropism, and to plan physiotherapy and rehabilitation programs. As a result, tropism should be questioned in patients suffering from LBP and limited lateral flexion. There is need for studies in which different evaluation and treatment methods are applied for tropism.